Performance of identity of Polish Tatars: from religious holidays to everyday rituals - Pawlic-Miśkiewicz, Barbara (Interdisciplinary studies in performance, 2018)
Introduction -- 1. Performance studies -- 2. The history of Tatars -- 3. Islam -- 4. Religious holidays -- 5. The rites of passage "rites of life"s turning points -- 6. Rituals of everyday life -- Conclusion -- Appendix 1. Biograms of persons -- A list of charts, pictures and illustrations -- Bibliography -- Index of names